2019
DOI: 10.3390/nu11102281
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sarcopenia in an IBD Population Attending an Italian Gastroenterology Tertiary Center

Abstract: (1) Background: There is growing interest in the assessment of muscular mass in inflammatory bowel disease (IBD) as sarcopenia is associated with important outcomes. The aim of the study was to evaluate the percentage of sarcopenia in IBD patients, characterizing methods for assessment and clinical symptoms associated to it. (2) Methods: Consecutive IBD patients accessing the Fondazione Policlinico Agostino Gemelli Istituto di Ricovero e Cura a Carattere Scientifico (IRCCS) were enrolled. Healthy patients, eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 16 publications
3
62
1
Order By: Relevance
“…It has been previously shown that low intensity exercise might reduce the risk of gastrointestinal diseases (i.e., colon cancer, diverticulosis, and inflammatory bowel disease), taking into account the strict correlation between skeletal muscle and GM [13,[17][18][19][20][21]. In more detail, physical activity might modify the transient stool time and the contact time between the pathogens and the gastrointestinal mucus layer, resulting in the gastrointestinal tract modifications above-mentioned [78].…”
Section: Physical Exercise and Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that low intensity exercise might reduce the risk of gastrointestinal diseases (i.e., colon cancer, diverticulosis, and inflammatory bowel disease), taking into account the strict correlation between skeletal muscle and GM [13,[17][18][19][20][21]. In more detail, physical activity might modify the transient stool time and the contact time between the pathogens and the gastrointestinal mucus layer, resulting in the gastrointestinal tract modifications above-mentioned [78].…”
Section: Physical Exercise and Gut Microbiotamentioning
confidence: 99%
“…Moreover, it has been recently hypothesized that physical exercise could also play a key role in modifying GM composition [17] and at the same time, it could reduce the risk of gastrointestinal diseases [18] such as inflammatory bowel disease, considering the emergent well-studied relationship between muscle function and GM [13,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Therapies for targeting inflammation are often the focus of current research, with less focus on the prevalence and impact of sarcopenia in IBD; despite a recent meta-analysis showing that 52% of patients with CD and 37% of patients with UC have sarcopenia [ 9 ]. These results are significant as sarcopenia is known to have a clear impact on quality of life, length of hospital stay, surgical outcomes, and mortality [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In CD patients, the hormones and proinflammatory cytokines act together on some cellular pathways to decrease protein synthesis and increase protein decomposition, resulting in muscular mass reduction (9,10). In addition, the protein intake reduces and/or the protein loss increases due to chronic or acute diarrhea in CD patients.…”
Section: Introductionmentioning
confidence: 99%